The Analysis of Current Variation in TIG (Tungsten Inert Gas) Welding on the Tensile Test Results of Aluminum 5083 Plates - Neida Abadia El Islami; Mukhnizar Mukhnizar; Zulkarnain Zulkarnain (The Future of Education Journal, 2025)
Tig welding (Tungsten Inert Gas) is one of the metal connections by welding on the surface of the plates connected to each other at the same time an electric current is passed so that the surface becomes hot and melts due to electrical resistance. Where Aluminum 5083 has a maximum tensile strength of 317 MPa (46,000Psi). This study aims to determine the results of tensile testing on welded joints using TIG welding (Tungsten Inert Gas) on Aluminum 5083 material. Quantitative research approach. The research technique used is an experiment, the research location was carried out in the mechanical engineering laboratory of Ekasakti University Padang and in the Mechanical Engineering Laboratory of ITP (Padang Institute of Technology). From the 100A current strength specimen, the average value was obtained: Maximum tensile stress ( , Yield Stress ( (2.354.4 N/mm2), Strain ( ) (0,02228%), Modulus of Elasticity ( ) (1.930.7360 N/mm2). And with a current of 120A, the average obtained is: Maximum Tensile Strength (  (62,9311 N/mm2), Yield Stress ( Strain ( ) (0.059.58%), Modulus of Elasticity ( ) (1,056,24 N/mm2). Based on the research results, it shows that the tensile strength results based on the current strength in TIG (Tungsten Inert Gas) welding, the average value with a welding current of 120A has a higher and greater tensile stress, yield stress, and strain compared to a current of 100A. This shows that the connection with a welding current of 120A is better than the welding current of 100A.